1997
DOI: 10.1172/jci119627
|View full text |Cite
|
Sign up to set email alerts
|

Biologically inactive growth hormone caused by an amino acid substitution.

Abstract: Short stature caused by biologically inactive growth hormone (GH) is characterized by lack of GH action despite high immunoassayable GH levels in serum and marked catch-up growth to exogenous GH administration. We found a heterozygous single-base substitution (A → G) in exon 4 of the GH-1 gene of a girl with short stature, clinically suspected to indicate the presence of bioinactive GH and resulting in the substitution of glycine for aspartic acid at codon 112. We confirmed the presence of mutant GH in the ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
5

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(65 citation statements)
references
References 27 publications
0
58
0
5
Order By: Relevance
“…Owing to the gene homology of human and mice, most research in vivo was found not to be influenced by species specificity of GH (Takahashi et al 1997). In this study, the intrinsic bionomics difference of human gastric cancer cell lines with different GHR expression was not excluded and will be further evaluated in the next paper.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the gene homology of human and mice, most research in vivo was found not to be influenced by species specificity of GH (Takahashi et al 1997). In this study, the intrinsic bionomics difference of human gastric cancer cell lines with different GHR expression was not excluded and will be further evaluated in the next paper.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, since the previously described p.D116A-GH harboring a missense mutation within the GH receptor-binding site 2 has a 5.7-fold lower affinity to the GH receptor than the WT-GH (15), this would argue for a functional importance of the D116 residue and implicate a similar functional alteration of the p.D116E-GH. In addition, although GH1 missense mutations reported to date are relatively rare (16), GH missense MTs, including those within or near the GH receptor binding site 2, frequently have a reduced or altered biological activity (2,4,(17)(18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, GH provocation tests are almost invariably performed in children with short stature (1), and measured serum GH values usually reflect GH bioactivities. However, in a rare condition known as 'bioinactive GH', discrepancy exists between measured GH values and GH bioactivities (2)(3)(4). Thus, this condition is associated with low insulin-like growth factor-1 (IGF-1) values, short stature, and good responses to GH therapy, in the presence of apparently normal to mildly elevated serum GH values.…”
Section: Introductionmentioning
confidence: 99%
“…descreveram duas crianças com fenótipo semelhante aos de crianças com deficiência de GH (baixa estatura severa e níveis baixos de IGF-I), mas que apresentavam secreção elevada de GH, e sugeriram que estas crianças possuíam uma molécula de GH biologicamente inativa (71). Mutações em heterozigose no gene GH-1 que causam a produção de uma molécula anômala de GH com estas características foram descritas em apenas dois casos na literatura (72,73). Esta molécula de GH anômala possui uma afinidade aumentada pela sua proteína carreadora (GHBP) e inibe a ligação da molécula de GH normal ao receptor ou ainda dificulta a dimerização do receptor.…”
Section: Gh Bioinativounclassified